P. 1
Useful Results in continuum mechanics

Useful Results in continuum mechanics

|Views: 101|Likes:
Published by b.banerjee.nz6800

More info:

Published by: b.banerjee.nz6800 on Sep 26, 2008
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

01/12/2013

pdf

text

original

Some Useful Results

Biswajit Banerjee
March 22, 2007
1 A spectral decomposition problem
• In one of Simo’s 1992 papers on plasticity [1] (p. 76) we find the statement that “An easy calculation then
gives the spectral decomposition”

∂τ
[φ(τ, q)] =
3
¸
A=1

∂β
A
[
´
φ(β
1
, β
2
, β
3
, q)] n
A
⊗n
A
. (1)
Here, τ is the Kirchhoff stress, q is a scalar internal variable, and φ is yield function. The spectral
decomposition of the Kirchhoff stress is given by
τ =
3
¸
A=1
β
A
n
A
⊗n
A
. (2)
Also, isotropy implies that the yield function φ can be expressed in terms of the principal values β
i
of τ such
that
φ(τ, q) =
´
φ(β
1
, β
2
, β
3
, q) . (3)
Let’s try to work out the easy calculation.
Using the chain rule, we have
∂φ
∂τ
=

´
φ
∂β
1
∂β
1
∂τ
+

´
φ
∂β
2
∂β
2
∂τ
+

´
φ
∂β
3
∂β
3
∂τ
or
∂φ
∂τ
=
3
¸
A=1

´
φ
∂β
A
∂β
A
∂τ
. (4)
Also, since
τ = β
1
n
1
⊗n
1
+ β
2
n
2
⊗n
2
+ β
3
n
3
⊗n
3
(5)
using the identity (since the eigenvectors n
A
are orthonormal)
(n
i
⊗n
i
) · (n
j
⊗n
j
) =

0 if i = j
n
i
⊗n
i
if i = j
(6)
we get
τ · (n
1
⊗n
1
) = β
1
n
1
⊗n
1
; τ · (n
2
⊗n
2
) = β
2
n
2
⊗n
2
; τ · (n
3
⊗n
3
) = β
3
n
3
⊗n
3
. (7)
1
Using the identity
(n
i
⊗n
i
) : (n
i
⊗n
i
) = 1 (8)
we then have
[τ · (n
1
⊗n
1
)] : (n
1
⊗n
1
) = β
1
; [τ · (n
2
⊗n
2
)] : (n
2
⊗n
2
) = β
2
; [τ · (n
3
⊗n
3
)] : (n
3
⊗n
3
) = β
3
. (9)
We can simplify these further by using the identities
(A· B) : C = A : (C · B
T
) ; n ⊗n = (n ⊗n)
T
; (n ⊗n) · (n ⊗n) = n ⊗n (10)
to get
τ : [(n
A
⊗n
A
) · (n
A
⊗n
A
)
T
] = τ : [(n
A
⊗n
A
) · (n
A
⊗n
A
)] = τ : (n
A
⊗n
A
) = β
A
; A = 1, 2, 3 (11)
Taking the derivatives of both sides with respect to τ, we get

∂τ
[τ : (n
A
⊗n
A
)] =
∂β
A
∂τ
; A = 1, 2, 3 (12)
Note here that as τ varies, the eigenvectors of τ (i.e., the n
A
s) also vary. So the derivatives will have the form
∂τ
∂τ
: (n
A
⊗n
A
) +τ :

∂τ
(n
A
⊗n
A
) =
∂β
A
∂τ
; A = 1, 2, 3 (13)
or,
I
s
: (n
A
⊗n
A
) +τ :

∂τ
(n
A
⊗n
A
) =
∂β
A
∂τ
; A = 1, 2, 3 (14)
where I
s
is the symmetric fourth-order identity tensor. Therefore,
∂β
A
∂τ
= n
A
⊗n
A
+τ :

∂τ
(n
A
⊗n
A
) . (15)
Plugging (15) into (4), we get
∂φ
∂τ
=
3
¸
A=1

´
φ
∂β
A
n
A
⊗n
A
+

´
φ
∂β
A
τ :

∂τ
(n
A
⊗n
A
) . (16)
Compare equations (16) and (1), shown below for your convenience.
∂φ
∂τ
=
3
¸
A=1

´
φ
∂β
A
n
A
⊗n
A
. (17)
You will see that the derivativ)es of the eigenvectors with respect to τ do not appear in Simo’s equation. This is an
approximation that Simo does not mention in his paper, i.e., that the values of n
A
are kept fixed when evaluating
the derivatives of φ. Or, am I missing something?
Indeed, there is an error in my analysis. Can you find out what it is?
Let us now try an alternative proof (hat tip Prof. Andrew Norris).
Since φ(τ) is isotropic, instead of working directly with the eigenvalues β
A
, we can work with the invariants of τ.
2
Recall that the basic invariants of τ are
I
τ
= tr(τ)
II
τ
=
1
2

I
2
τ
− tr(τ
2
)

III
τ
=
1
3

tr(τ
3
) − I
3
A
+ 3 I
A
II
A

(18)
Therefore, the yield function can also be represented as
φ(τ, q) = φ(α
1
, α
2
, α
3
, q) (19)
where
α
1
= tr(τ) ; α
2
=
1
2
tr(τ
2
) ; α
3
=
1
3
tr(τ
3
) . (20)
Differentiating with respect to τ, we get
∂φ
∂τ
=
∂φ
∂α
1
∂α
1
∂τ
+
∂φ
∂α
2
∂α
2
∂τ
+
∂φ
∂α
3
∂α
3
∂τ
. (21)
Now,
∂α
1
∂τ
=
∂[tr(τ)]
∂τ
= 1 ;
∂α
2
∂τ
=
1
2
∂[tr(τ
2
)]
∂τ
= τ ;
∂α
3
∂τ
=
1
3
∂[tr(τ
3
)]
∂τ
= τ
2
. (22)
Therefore,
∂φ
∂τ
=
∂φ
∂α
1
1 +
∂φ
∂α
2
τ +
∂φ
∂α
3
τ
2
. (23)
Let us now express τ in terms of its spectral representation to get
1 =
3
¸
A=1
n
A
⊗n
A
=
3
¸
A=1
β
0
A
n
A
⊗n
A
τ =
3
¸
A=1
β
1
A
n
A
⊗n
A
τ
2
=
3
¸
A=1
β
2
A
n
A
⊗n
A
(24)
Let us also express the α
i
, i = 1, 2, 3 in terms of the spectral representation of τ, i.e.,
α
1
= tr(τ) =
3
¸
A=1
β
A
tr(n
A
⊗n
A
) =
3
¸
A=1
β
A
α
2
=
1
2
tr(τ
2
) =
1
2
3
¸
A=1
β
2
A
tr(n
A
⊗n
A
) =
1
2
3
¸
A=1
β
2
A
α
3
=
1
3
tr(τ
3
) =
1
3
3
¸
A=1
β
3
A
tr(n
A
⊗n
A
) =
1
3
3
¸
A=1
β
3
A
(25)
Therefore,
∂α
1
∂β
A
= 1 = β
0
A
;
∂α
2
∂β
A
= β
A
= β
1
A
;
∂α
3
∂β
A
= β
2
A
. (26)
3
Plugging these into (24) gives
1 =
3
¸
A=1
∂α
1
∂β
A
n
A
⊗n
A
τ =
3
¸
A=1
∂α
2
∂β
A
n
A
⊗n
A
τ
2
=
3
¸
A=1
∂α
3
∂β
A
n
A
⊗n
A
(27)
Substituting into (23), we get
∂φ
∂τ
=
∂φ
∂α
1
3
¸
A=1
∂α
1
∂β
A
n
A
⊗n
A
+
∂φ
∂α
2
3
¸
A=1
∂α
2
∂β
A
n
A
⊗n
A
+
∂φ
∂α
3
3
¸
A=1
∂α
3
∂β
A
n
A
⊗n
A
(28)
or,
∂φ
∂τ
=
3
¸
A=1
¸
∂φ
∂α
1
∂α
1
∂β
A
+
∂φ
∂α
2
∂α
2
∂β
A
+
∂φ
∂α
3
∂α
3
∂β
A

n
A
⊗n
A
(29)
or,
∂φ
∂τ
=
3
¸
A=1

´
φ
∂β
A
n
A
⊗n
A
(30)
We finally have the correct expression!
• In the operator split algorithm in [1] we have the the following expression for the algorithmic flow rule
b
e
= exp

−2˙ γ∆t
∂φ
∂τ

· (b
e
)
trial
(31)
If the spectral decompositions of b
e
and τ are
b
e
=
3
¸
A=1
λ
2
A
n
A
⊗n
A
; τ =
3
¸
A=1
β
A
n
A
⊗n
A
(32)
and
∂φ
∂τ
=
3
¸
A=1

´
φ
∂β
A
n
A
⊗n
A
(33)
show that
(b
e
)
trial
=
3
¸
A=1
¸
λ
2
A
exp

2˙ γ∆t

´
φ
∂β
A
¸
n
A
⊗n
A
. (34)
From (31), we have
(b
e
)
trial
= exp

2˙ γ∆t
∂φ
∂τ

· b
e
= exp

κ
∂φ
∂τ

· b
e
(35)
where
κ := 2˙ γ∆t . (36)
4
Expanding in an infinite series, we have
exp

κ
∂φ
∂τ

= 1 + κ
∂φ
∂τ
+
κ
2
2

∂φ
∂τ

2
+
κ
3
3!

∂φ
∂τ

3
+ . . . (37)
Define
α
A
:=

´
φ
∂β
A
. (38)
Then,
∂φ
∂τ
=
3
¸
A=1
α
A
n
A
⊗n
A
;

∂φ
∂τ

2
=
3
¸
A=1
α
2
A
n
A
⊗n
A
;

∂φ
∂τ

3
=
3
¸
A=1
α
3
A
n
A
⊗n
A
; . . . (39)
Therefore,
exp

κ
∂φ
∂τ

= 1 +
3
¸
A=1
¸
κ α
A
+
κ
2
2
α
2
A
+
κ
3
3!
α
3
A
+ . . .
¸
n
A
⊗n
A
. (40)
Since
1 =
¸
A
n
A
⊗n
A
(41)
we then have
exp

κ
∂φ
∂τ

=
3
¸
A=1
¸
1 + κ α
A
+
(κ α
A
)
2
2
+
(κ α
A
)
3
3!
+ . . .
¸
n
A
⊗n
A
=
3
¸
A=1
e
κ α
A
n
A
⊗n
A
. (42)
Using the spectrla decomposition of b
e
, we get
exp

κ
∂φ
∂τ

· b
e
=
¸
3
¸
A=1
exp(κ α
A
) n
A
⊗n
A
¸
·
¸
3
¸
B=1
λ
2
B
n
B
⊗n
B
¸
. (43)
From the identity
(n
i
⊗n
i
) · (n
j
⊗n
j
) =

0 if i = j
n
i
⊗n
i
if i = j
(44)
we then get
exp

κ
∂φ
∂τ

· b
e
= e
κ α
1
λ
2
1
n
1
⊗n
1
+ e
κ α
2
λ
2
2
n
2
⊗n
2
+ e
κ α
3
λ
2
3
n
3
⊗n
3
=
3
¸
A=1
λ
2
A
e
κ α
A
n
A
⊗n
A
. (45)
Therefore, from (35)
(b
e
)
trial
=
3
¸
A=1
¸
λ
2
A
exp

2˙ γ∆t

´
φ
∂β
A
¸
n
A
⊗n
A
. (46)
References
[1] J. C. Simo. Algorithms for static and dynamic multiplicative plasticity that preserve the classical return
mapping algorithms of the infinitesimal theory. Comp. Meth. Appl. Mech. Engrg., 99:61–112, 1992.
5

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->